The Effect of Ketamine infusions on suicidal ideation in various mood disorders - Muhammad Bin Mobin; Abid , Zainab; Saqib, Sameen (Journal of the Pakistan Medical Association, 2025)
Borderline Personality Disorder (BPD) is characterised by altered perception of self, mood changes, and suicidal ideation. The traditional treatments of BPD, including psychotherapy, fail to provide an immediate response in susceptible patients. However, recent literature has shed light on the use of Ketamine as intervention for suicidal ideation in BPD patients, as well as for patients with Major Depressive Disorder (MDD). Studies have shown that administering low doses of Ketamine intravenously has profound impact on reducing suicidality in susceptible patients. The mechanism of action of Ketamine is thought to be its regulation of neurotrophic factors, hence, eliciting a rapid response. Furthermore, Ketamine has also proved beneficial in alleviating other symptoms of BPD including mood dysregulation and impulsive behaviour. Provided the evidence, Ketamine could revolutionise the emergency management of suicidality; however, further research is required to establish its dose, safety, and contraindications. Keywords: Ketamine, Mood disorders, Major depressive disorder, Borderline personality disorder, Suicidal ideation.